Current Characteristics of Native Valve Infective Endocarditis in Japan: Has the Prevalence of Atrial Valve Infection and Microbiology Changed Over the Last 10 Years?. Issue 1 (January 2019) - Kobayashi, Daiki; Kuriyama, Nagato; Takahashi, Osamu; Hirano, Keita; Nanki, Nobuki; Arioka, Hiroko; Osugi, Yasuhiro; Yokota, Kyoko
Abstract : Objectives: The aim of this study was to evaluate the characteristics of infective endocarditis (IE) over 10 years in Japan, where many elderly people are expected to develop aortic valvular diseases. Methods: We conducted a retrospective cohort study with all IE adult patients who were admitted to St Luke's International Hospital in Tokyo, Japan, from 2003 to 2015. All patients who were clinically diagnosed with IE by infectious disease doctors were enrolled. Our primary outcomes were in-hospital all-cause mortality and an indication for valvular surgery. Secondary outcomes were the types of infected valves and causative pathogens. Results: A total of 101 patients had IE. The mean age was 67.4 (SD, 18.3) years, and 60.4% were men. In terms of outcomes, dose-dependent trends were observed in the various age groups. The trend test for operation by age group was significant ( P = 0.03), but it was not for mortality ( P = 0.18), Staphylococcus aureus infection ( P = 0.25), or for atrial valve infection ( P = 0.17). Patients who were younger than 40 years tended to have operations more frequently than did those who were 65 years or older (odds ratio [OR], 4.89; 95% confidence interval [CI], 1.01–23.75). Those whose body mass index was 25 kg/m 2 or higher (OR, 7.18; 95% CI, 1.03–50.26) and those who had diabetes (OR, 6.29; 95% CI, 1.82–21.72) were more likely to be infected by S. aureus . Those who had hypertension tended to suffer from aortic valve IE (OR, 3.36; 95% CI, 1.05–10.75). Conclusion: Elderly patients had lower rates of surgical intervention but similar mortality to younger patients. Obesity and diabetes were risk factors for S. aureus IE, and hypertension was a risk factor for aortic valve IE.